In my notes it said that ${d^2y\over dx^2} -xy=0$ has an irregular singular point at $x=\infty$.

It was illustrated by doing a transformation $y(x)=w(t)$ with $t=\frac{1}{x}$. But I don't understand, how did they get

${dy\over dx} =-t^2 {dw\over dt}$ and ${d^2y\over dx^2}=t^4 {d^2w\over dt^2}+2t^3 {dw\over dt}$?

And how did they get

${d^2w\over dt^2} + \frac{2}{t}{dw\over dt}+\frac{1}{t^5}w=0$?

  • 1
    $\begingroup$ They used the chain rule. $\frac{\mathrm dy}{\mathrm dx}=\frac{\frac{\mathrm dw}{\mathrm dt}}{\frac{\mathrm dx}{\mathrm dt}}$. $\endgroup$ – J. M. isn't a mathematician May 12 '12 at 16:54
  • $\begingroup$ ...and that particular equation you're looking at is Airy's equation. $\endgroup$ – J. M. isn't a mathematician May 12 '12 at 16:55

Before we start, let's use $y'', y', w', w''$, etc. just for efficiency's sake.

So, you know that the solution to the differential equation $y'' - xy = 0$ comes with two linearly independent solutions called the Airy $Ai(x)$ and the Airy $Bi(x)$ functions.

We are told that the substitution is $y(x) = w(x)$. Making this substitution, find $y'$ using the chain rule $dy/dx = (dw/dt)(dx/dt)$. This is the same as $y' = x'w'$ which gives us $y' = (-t^2)w'$. Notice that we want to get them equal, which is why the function becomes $-t^2$ and not $-1/t^2$. Now, notice that for example when $y=uv$, where $u,v$ are both functions, by chain rule we have $y'=u'v + v'u$. In the same manner, $y'=(-1/t^2)w'$ becomes $y''=(-1/t^2)'w' + (-1/t^2)w''$. Substituting to maintain equivalence, we see that $y'' = t^4w'' + 2t^3w'$ (check yourself).

Substitute the newly found equivalencies into the original form of $y''-xy = 0$ and you will see that $w'' + (2/t)w' + (1/t^5)w = 0$.

Now, you can surely see that when $x=∞$, t becomes 0. As you probably know well, $P(x)(x-x_0)$ and $Q(x)(x-x_0)^2$ must be singular in order to be irregular singular. Well, once you plug in $t=0$ you can surely see that $Q(x)$ part is still singular, and therefore this function is irregular at $x=∞$

| cite | improve this answer | |
  • $\begingroup$ Thanks for explaining it to me Nico! I understood it now and got the result! $\endgroup$ – Jonathan May 13 '12 at 20:23

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.